A new species and notes on the subgenus Deltochilum (Deltochilum) Eschscholtz, 1822 (Coleoptera: Scarabaeidae: Scarabaeinae: Deltochilini) - Génier, François (Zootaxa, 2012)
Deltochilum eurymedon new species is described and illustrated. Two new synonymies are proposed, Deltochilum (Telhyboma)Kolbe, 1893 = Deltochilum (Deltochilum) Eschscholtz, 1822 and D. (D.) scabriusculum montanum Howden, 1966 = D. (D.)scabriusculum Bates, 1887. Diagnostic characters are given and aedeagi are illustrated for each species currently included in the subgenus Deltochilum. Finally, distributional data and literature records are also provided.